ANALYSIS OF TRACE ELEMENTS IN EPIPHYTIC LICHENS FROM KELANTAN AND TERENGGANU, MALAYSIA - Wee, Boon Siong; Shakirah, Abd Shukor; Azian, Hashim; Shamsiah, Abdul Rahman; Md Suhaimi, Elias; Nazaratul Ashifa, Abdullah Salim (Department of Wildlife and National Parks, 2023)
Lichens are known among the first organisms to be used as biomonitors to assess level of environmental pollution originated from anthropogenic and natural sources. In this study, we reported for the first time multielement data of lichens collected from Kelantan and Terengganu, Malaysia. The trace elements in the lichens are then compared with data from the unpolluted areas. Samples were collected from 2 locations in Kelantan and 4 locations in Terengganu. The samples were analyze using Instrumental Neutron Activation Analysis (INAA) method and 20 elements were identified (Al, As, Ce, Co, Cr, Cs, Eu, Fe, Hf, Hg, K, La, Mn, Na, Rb, Se, Sc, Th, V, Zn). Result showed that most of the elements were within the concentration ranges of the baseline data from the unpolluted areas. The enrichment factors (EF) of trace elements in lichens showed that most of the elements were within the ranges except for As (EF: 3.8 – 30), which was found to be slightly enriched compared to baseline data (EF: 1.7 – 5.2). Other elements such as Hg (EF: 23 – 210) and Se (EF: 90 – 457) were also enriched.The toxic elements (As, Hg, Se) are probably related to long distance transport from other anthropogenic sources. Trace element data obtained using INAA were very useful in identifying potential trace element pollutants in the sampling areas of Kelantan and Terengganu.